SUSTAINABILITY CLASSIFICATION OF AGRICULTURAL PRODUCTION UNITS IN THE ARARAS NORTE IRRIGATED DISTRICT, CEARÁ, BRAZIL - ANDRADE, Eunice Maia de; CARNEIRO NETO, José Alves; ROSA, Morsyleide de Freitas; PALÁCIO, Helba Araújo Queiroz; RODRIGUES, Joseilson Oliveira (Scientia Agraria, 2009)
The aim of this study was to identify the determinant sustainability factors in agricultural production units in the Araras North Irrigated District, as well as to develop a sustainability index applying multivariate statistical technique. The approach was based on a cross-over form applied to 47 irrigators that live in the Araras North Irrigated District located in the uplands of the Acaraú watershed, Ceará, Brazil. According to the results the family education level was the major factor in determining the sustainability of the agricultural production units in the Araras North Irrigated District. The second factor was mainly related to the trade processes (selling difficulties and production transportation); while the third one was defined by the variables that express the irrigator’s family condition (the youth of the community involvement and their interest in continuing the agricultural activities). The last factor was pointed out by variables related to natural resources conservation technique. The developed Sustainability Index from selected determinant factors registered that 27.7% of the agricultural production units were classified as sustainables, 25.5% presented a threatened sustainability and 14.9% had a compromised sustainability. Among the 47 units, 11 were classified as unsustainable, which represents 23.4% of them.